Myeloperoxidase-derived hypochlorous acid antagonizes the oxidative stress-mediated activation of iron regulatory protein 1 - Mütze, Sabine; Hebling, Ulrike; Stremmel, Wolfgang; Wang, Jian; Arnhold, Jürgen; Pantopoulos, Kostas; Mueller, Sebastian (The journal of biological chemistry, 2003)
Hypochlorous acid (HOCl) is a highly reactive product generated by the myeloperoxidase reaction during the oxidative burst of activated neutrophils, which is implicated in many bactericidal and cytotoxic responses. Recent evidence suggests that HOCl may also play a role in the modulation of redox sensitive signaling pathways. The short half-life of HOCl and the requirement for a continuous presence of H2O2 as a substrate for its myeloperoxidase-catalyzed generation make the study of HOCl-mediated responses very difficult. We describe here an enzymatic model consisting of glucose/glucose oxidase, catalase, and myeloperoxidase (GOX/CAT/MPO) that allows the controlled generation of both HOCl and H2O2 and thus, mimics the oxidative burst of activated neutrophils. By employing this model we show that HOCl prevents the H2O2-mediated activation of iron regulatory protein 1 (IRP1), a central post-transcriptional regulator of mammalian iron metabolism. Activated IRP1 binds to ®iron-responsive elements” (IREs) within the mRNAs encoding proteins of iron metabolism and thereby controls their translation or stability. The inhibitory effect of HOCl is not a result of a direct modification of IRP1 by this oxidant. Kinetics experiments provide evidence that HOCl intervenes with the signaling cascade, which results in the activation of IRP1. We further demonstrate that HOCl antagonizes the H2O2-mediated increase in the levels of transferrin receptor, which is a downstream target of IRP1. Our findings suggest that HOCl can modulate signaling pathways in a concerted action with H2O2. The GOX/CAT/MPO system provides a valuable tool for studying the regulatory function of HOCl.
Gesehen am 30.05.2022